Peran Pendidikan Islam dalam Mendukung Pencapaian SDGs : Studi Kepustakaan - Adelia Putri; Kamilatul Hayati; Riri Novia Sari Hasibuan; Herlini Puspika Sari (Jurnal Budi Pekerti Agama Islam, 2025)
This study explores the role of Islamic education in supporting the achievement of the Sustainable Development Goals (SDGs) through a library research approach. Islamic education, with its emphasis on moral, spiritual, and social values, aligns closely with the principles of sustainable development. The study reveals that Islamic teachings on justice, equality, social responsibility, and environmental stewardship are in harmony with the goals outlined in the SDGs. Islamic educational institutions contribute to poverty alleviation, environmental awareness, and gender equality through curriculum content and practical programs rooted in Islamic values. However, challenges such as limited curriculum integration and lack of teacher capacity remain obstacles. Therefore, it is essential to enhance the curriculum, empower educators, and build partnerships between Islamic educational institutions and broader development stakeholders to ensure Islamic education becomes a significant agent in achieving the global goals.